Implementation of the Habituation Method in improving Disciplinary Character in Elementary Schools - Romiyatun Romiyatun; Wakhudin Wakhudin (Proceedings Series on Social Sciences & Humanities, 2023)
The character of discipline is behavior that reflects obedience in carrying out applicable regulations. The character of discipline is important. Without awareness of the necessity of carrying out predetermined rules, it will require a method of habituation so that it can form a strong student character. The purpose of this study is to describe habituation methods in improving student discipline character and the impact of habituation method implementation in improving student discipline character. The research method used is qualitative research with a case study approach using data collection techniques in the form of interviews, observations and documentation studies. The data analysis technique used in this study is Milles and Huberman's interactive analysis model. From this study, it can be concluded that the process of implementing habituation methods in improving disciplinary character has run as expected. This is evidenced by the achievement of 2 disciplines, namely the discipline of obeying the rules of discipline and the discipline of time.